The Role of Demand toward Employee’s Wage Change: An Islamic Perspective - Noviyanti, Ririn (Falah: Jurnal Ekonomi Syariah, 2017)
An employee must get a justice wage according their contribution to the company. But in reality, the employee get a stabil wage even in increasing of demand, and force them to receive a lower wage when the company in decreasing of demand. It’s a kind of unjustify according the contribution that the employee have given. This study is the research literature. The data in this study are obtained by using the documentary method, to search for data about the role of demand on wage levels. These data are analyzed by using descriptive method of content analysis to determine the contents of the three variables. The role of demand toward employee wage change in Islamic economics can be explained from two forms. First, demand increase for shared and unshared, demand increase for shared than the employee will get the additional wage from increasing demand, demand increase unshared, then the employee will get the stable wage due to additional company’s capital. Second, Demand decrease shared and unshared, demand decrease shared, then the employee will get the  lower wage, decrease unshared, then the employee will get the stable wage caused the company should to reduce the company’s capital by requirement the additional employee hard work.